Usefulness of Leukocyte Esterase Test Versus Rapid Strep Test for Diagnosis of Acute Strep Pharyngitis - Kumara V. Nibhanipudi MD (SAGE Publishing, 2015)
Objective: A study to compare the usage of throat swab testing for leukocyte esterase on a test strip(urine dip stick-multi stick) to rapid strep test for rapid diagnosis of Group A Beta hemolytic streptococci in cases of acute pharyngitis in children. Hypothesis: The testing of throat swab for leukocyte esterase on test strip currently used for urine testing may be used to detect throat infection and might be as useful as rapid strep. Methods: All patients who come with a complaint of sore throat and fever were examined clinically for erythema of pharynx, tonsils and also for any exudates. Informed consent was obtained from the parents and assent from the subjects. 3 swabs were taken from pharyngo-tonsillar region, testing for culture, rapid strep & Leukocyte Esterase. Results: Total number is 100. Cultures 9(+); for rapid strep== 84(-) and16 (+); For LE== 80(-) and 20(+) Statistics: From data configuration Rapid Strep versus LE test don't seem to be a random (independent) assignment but extremely aligned. The Statistical results show rapid and LE show very agreeable results. Calculated Value of Chi Squared Exceeds Tabulated under 1 Degree Of Freedom (P<.0.0001) reject Null Hypothesis and Conclude Alternative Conclusions: Leukocyte esterase on throat swab is as useful as rapid strep test for rapid diagnosis of strep pharyngitis on test strip currently used for urine dip stick causing acute pharyngitis in children.